Epidemiological assessment of the influence of drinking water nitrates on decentralized water supply sources on the health of young children in Cherkasy region (Environment & Health, 2019)
Objective: to carry out an epidemiological assessment of the effect of nitrates of drinking water from decentralized sources of water supply on the health of young children and pregnant women of Cherkasy region.Materials and methods. Determination of the concentration of nitrates in drinking water of decentralized and centralized sources of water supply was carried out in accordance with the State Standard of Ukraine ISO 7890-1: 2003. Water quality. Determination of nitrates. Part 1. Spectrometric method using distilled 4-fluorophenol (ISO7890-1 1986. IDT) and GOST 18826-73 Drinking water. Methods for the determination of nitrates. In addition, statistical, hygienic, epidemiological, bibliographic, analytical research methods were used.Results. In 2018, the State Institution "Cherkassy Regional Laboratory Center of the Ministry of Health of Ukraine" investigated 8173 food samples (vegetables and fruits), water from centralized and decentralized sources of water supply, of which 2579 are foodstuffs, 2390 are decentralized water and 3204 – centralized water sources. In food products in 0,5% of samples, the content of nitrates was higher than the maximum permissible, and in water of centralized sources - in 4%, decentralized sources - in 30%.Conclusions. It has been established that the main source of nitrates in the human body is drinking water from decentralized sources of water supply. The occurrence of nitrate poisoning in young children should be regarded as a threat to their health and life.
Keywords: nitrates; drinking water; health; young children; methemoglobinemia; methemoglobin